Gluten free products: a challenge for the food industry - Villanueva-Flores, Rafael (2017)
There is an interesting market for the food industry in gluten free consumers. However, it is not easy to get gluten-free products with similar characteristics and cost to those with gluten. It is important that food labels mention the allergens used during production or if production lines, in which allergen ingredients are processed, are used, so that consumers will be well informed an avoid products that may be harmful.